2022
DOI: 10.2340/17453674.2021.1006
|View full text |Cite
|
Sign up to set email alerts
|

Risk of total knee replacement after proximal tibia fracture: a register-based study of 7,841 patients

Abstract: Background and purpose — Post-traumatic knee osteoarthritis following proximal tibia fracture (PTF) is a common complication that may lead to total knee replacement as secondary treatment (TKRS). We determined the risk of TKRS following PTF, whether treated nonoperatively or operatively, and compared the results with a 38-fold control group without prior PTF. Patients and methods — We identified all patients over 18 years of age in Finland with PTF treated during the period 2009–2018 from the Finnish Hospital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 16 publications
(43 reference statements)
1
11
1
Order By: Relevance
“…This was statistically significant at the 2 years follow‐up and a tendency at 5‐, 7‐ and 10‐years follow‐up. Similar results were found in other publications [5, 8, 25, 29]. Higher age has a negative impact on the repair cells, extracellular matrix, blood supply and molecules and their receptors [15].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This was statistically significant at the 2 years follow‐up and a tendency at 5‐, 7‐ and 10‐years follow‐up. Similar results were found in other publications [5, 8, 25, 29]. Higher age has a negative impact on the repair cells, extracellular matrix, blood supply and molecules and their receptors [15].…”
Section: Discussionsupporting
confidence: 91%
“…A recently published systematic review stated a conversion rate of about 5% [8]. The four largest studies in this review reported a percentage between 4.4% and 7.3% with a mean follow-up between 5.1 years and 13.9 years [5,25,28,29]. These values are slightly lower compared with our percentages and follow-up.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…However, while radiographic signs of post-traumatic osteoarthritis after proximal tibial fracture are common, symptomatic osteoarthritis leading to total knee replacement is still a rare event. While the very low TKA conversion rate in earlier publications may be due to the limited experience with revision knee arthroplasty at that time ( 84 ), even recent studies report conversion rates below 10% at 5–10 years of follow-up ( 90 , 91 ). Although risk is thought to increase with age, geriatric patients generally do well with ORIF after tibial plateau fracture ( 90 , 92 , 93 ).…”
Section: Discussionmentioning
confidence: 97%
“…Elsoe et al studied 7,950 TPFs, regardless of treatment, from the Danish Patient Register and found a 5.7% conversion rate to TKA with a mean follow-up of 13.9 years [ 11 ]. A Finnish hospital discharge register report found a conversion rate to TKA of 4.4% in 7,701 patients after TPF with a mean follow-up of 5.1 years [ 20 ]. The conversion rate was 5.0% in the surgically treated group.…”
Section: Discussionmentioning
confidence: 99%